A new RS steganalysis algorithm of detecting UnderMP3Cover - Jian ZHANG; Rangding WANG; Diqun YAN (Dianxin kexue)
A new RS steganalysis algorithm to attack UnderMP3Cover was proposed.By analyzing the error caused by the RS algorithm,the choice of resolution function,the initial bias and the fitting method were modified,the flip operator was also selected in the experiment.Experimental results demonstrate that the proposed method can estimate the length of embedded message effectively and the average error reduces to 2%,which is better than the existing algorithms.